Community Based Management for Forest Conservation and Livelihood Improvement: A Comparative Analysis from Forests in Myanmar - Basnet, Shambhavi; Sharma, Prashanti; Timalsina, Niroj; Khaine, Inkyin (Journal of Forest and Livelihood, 2018)
Myanmar has the world’s third largest deforestation rate with one of the major causes being peoples’ dependency on forest products. Fuelwood is still used in large amounts for various household activities in rural areas of Myanmar. This paper deals with the categorization of forest into conserved forest and open access and the study of fuelwood dependency in these two access regimes in the Taunggyi district of Myanmar. A significant difference is observed in the aboveground biomass levels and fuelwood consumption in these two access regimes. Various socio-economic parameters and forest indicators were also evaluated using field derived information. The study recommends the establishment of community forestry management system for improving forest condition and livelihood opportunities.